Mosaic Intronic NIPBL Variant in a Family With Cornelia de Lange Syndrome - Krawczynska, Natalia; Kuzniacka, Alina; Wierzba, Jolanta; Parenti, Ilaria; Kaiser, Frank J.; Wasag, Bartosz (Frontiers in Genetics, 2018)
Cornelia de Lange Syndrome (CdLS) is a well described multiple malformation syndrome caused by alterations in genes encoding subunits or regulators of the cohesin complex. In approximately 70% of CdLS patients, pathogenic NIPBL variants are detected and 15% of them are predicted to affect splicing. Moreover, a large portion of genetic variants in NIPBL was shown to be somatic mosaicisms. Here we report two family members with different expression of CdLS phenotype. In both individuals, a c.869-2A>G (r.869_1495del) substitution was detected, affecting a conserved splice-acceptor site. Next generation sequencing (NGS) revealed the presence of somatic mosaicism in the mother. The substitution was detected in 23% of the sequencing reads using DNA derived from blood samples and 51% in DNA from buccal swabs. The analysis of blood DNA of the affected son did not indicate for a somatic mosaicism. Correlation of molecular and clinical data revealed that various distribution of genetic alteration in different cell types had an impact on the expression of observed clinical features in both individuals.